Competitive growth of crystals in vanadium–chromium slag. Issue 33 (18th July 2016) - Diao, Jiang; Zhou, Wang; Gu, Pan; Ke, Zhaoqun; Qiao, Yong; Xie, Bing
Abstract : The competitive growth of crystals in vanadium–chromium slag was investigated. The component with the highest melting temperature dominates the crystallization process. Abstract : Based on the classic kinetic theory of crystallization, we have developed a mathematical model to describe the crystallization behavior of crystals in complex vanadium–chromium slag systems. The results show that the crystallization rates of spinels, olivines and augites are dominated by the component with the highest melting point. The sequence of the crystallization ability of crystals in vanadium–chromium slag is as follows: FeCr2 O4 > Mg2 SiO4 > FeV2 O4 > MgSiO3 > Fe2 TiO4 > Mn2 SiO4 > MnSiO3 > Fe2 SiO4 . The optimum temperature ranges for the crystallization of these crystals are 1497–1547 K, 1380–1430 K, 1301–1351 K, 1192–1242 K, 1098–1148 K, 1069–1119 K, 1038–1088 K and 985–1035 K, respectively. We also find that with the increase in Cr2 O3 /V2 O3 and decrease in SiO2 /FeO, the total crystallization rate of spinels increases remarkably, while the TiO2 content has little effect on the crystallization of spinels in vanadium–chromium slag.